2019
DOI: 10.1002/pits.22301
|View full text |Cite
|
Sign up to set email alerts
|

An alternative to fortified schools: Using crime prevention through environmental design (CPTED) to balance student safety and psychological well‐being

Abstract: In response to tragic school shootings, heightened attention has been devoted to making schools safer through the implementation of security features. However, excessive security measures have a negative impact on school climate, student functioning, and academic achievement. Therefore, there is a critical need to design schools that are safe and secure, yet also welcoming and comfortable. As a promising approach in this regard, crime prevention through environmental design (CPTED) is an architectural philosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
(84 reference statements)
2
14
0
2
Order By: Relevance
“…Based on an architectural philosophy that aims to prevent criminal or anti-social behavior through the climate, CPTED primarily focused on natural surveillance, access control, and territorial reinforcement [ 35 ], considering four main mechanisms: space design, space use, circulation and circulation patterns, and territorial characteristics and space deterioration. The benefits of CPTED in reducing the incidence of BP and school violence have been largely demonstrated (e.g., [ 32 , 36 ]). When analyzing the associations between the physical attributes of schools and violence-related behaviors, Vagi et al [ 32 ], found an association between better scores on the CPTED and a lesser probability of students missing school due to safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…Based on an architectural philosophy that aims to prevent criminal or anti-social behavior through the climate, CPTED primarily focused on natural surveillance, access control, and territorial reinforcement [ 35 ], considering four main mechanisms: space design, space use, circulation and circulation patterns, and territorial characteristics and space deterioration. The benefits of CPTED in reducing the incidence of BP and school violence have been largely demonstrated (e.g., [ 32 , 36 ]). When analyzing the associations between the physical attributes of schools and violence-related behaviors, Vagi et al [ 32 ], found an association between better scores on the CPTED and a lesser probability of students missing school due to safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…Wang y Degol (2016) identificaron en su revisión teórica con 327 fuentes bibliográficas que el clima escolar se puede englobar en cuatro dimensiones: a) clima académico, b) comunidad, c) seguridad y d) ambiente institucional, lo que corrobora la multidimensionalidad del constructo. Por su parte, Kutsyuruba, Klinger y Hussain (2015) también analizaron la multidimensionalidad del clima escolar y propusieron tres grandes áreas: A) social, B) académica y C) física, las cuales abarcan las dimensiones y dominios propuestos por otros autores (Benbenishty, Astor, Roziner & Wrabel, 2016;Lamoreaux & Sulkowski, 2020;Wang & Degol, 2016), como se puede apreciar en la descripción que se hace a continuación:…”
Section: Multidimensionalidad Del Clima Escolarunclassified
“…Se refiere al entorno institucional, es decir, a los aspectos organizativos, físicos y materiales de la escuela. Algunos estudios (Lamoreaux & Sulkowski, 2020;Kutsyuruba et al, 2015) han reconocido que las condiciones de infraestructura y el mobiliario de la escuela e incluso del salón de clase, pueden influir en la calidad del ambiente escolar.…”
Section: C) áRea Física Del Clima Escolarunclassified
“…The CPTED concept mainly affects external threats. Among the general principles of the CPTED concept, which are most relevant to school design, can be included: Territoriality, Natural Surveillance, Natural access control, and Maintenance (Image/Space management) [27,28]. The following table shows the elements of the individual CPTED principles, which were qualitatively evaluated on a selected object [10,27,29,30,31,32].…”
Section: Application Of the Cpted On A Selected Case Studymentioning
confidence: 99%